A DELAYED DIAGNOSIS OF CONGENITAL DYSERYTHROPOIETIC ANAEMIA IN EARLY ADULTHOOD AFTER YEARS OF TRANSFUSION THERAPY - Shafqat, Jawad; Shabbir, Muhammad Usama Bin; Ali, Sundus; Abbasi, Sikandar Ajmal; Huraira, Abu; Raza, Muhammad Jazib; Khan, Muhammad Safeerullah (Journal of Ayub Medical College Abbottabad, 2024)
Congenital dyserthropoietic anaemias (CDAs) constitute a diverse category of anaemia marked by differing levels of ineffective erythropoiesis and subsequent development of secondary hemochromatosis. Congenital dyserthropoietic anaemia (CDA) type 2 is an uncommon genetic disorder characterized by mild to severe anaemia. The rarity of this condition can contribute to frequent misdiagnoses, as the morphological abnormalities and the clinical features it presents are commonly shared with other anaemias that are clinically related. Therefore, we report a case involving a 24-year-old female patient with complaints of epigastric pain, vomiting, weight loss, and a history of frequent blood transfusions. A bone marrow biopsy confirmed the diagnosis of Congenital Dyserthropoietic Anaemia type 2. The management approach involved interdisciplinary support and regular psychotherapy for both the patient and her family.